Strategi Alih Tutur pada Gelar Wicara Mata Najwa Episode “Beres-Beres Kursi Menteri Kesehatan”: Kajian Analisis Percakapan - Putra, Pebri Prandika (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This research investigates the dynamics of turn-taking within a talk show context, specifically focusing on the